(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: This research discusses the political role played by France in its relationship with the State of Tripoli during Al-Qaramanli reign from 1711 to 1835, as this period was full of events and relations between the two countries. The researcher pointed out to several points, including the definition of Al-Qaramanli family, its roots and historical origins, and how they settled in Libya. Then the researcher mentioned the factors for the arrival of the Al-Qaramanli to power and the reasons for the Ottoman Empire’s recognition of them. The researcher further mentioned the most prominent rulers of the Al-Qaramanli family, the first of whom was Pasha Ahmed Al-Qaramanli 1711-1745. In addition, the researcher presented the reasons for the French-Tripoli rapprochement / moving to the French diplomatic representation in Libya in terms of the most prominent diplomats and methods of selecting consuls, and also referred to the nature of the relationship between France and Tripoli during the reign of Ahemed Pasha and during the reign of Yusouf Basha. The researcher also referred to the French campaign against Egypt and the position of Yusuof Pasha on it. Finally, the researcher set a conclusion summarizing the most prominent points that were talked about in the research and then included the list of references.